Inovasi dalam Penyelesaian Sengketa: Pendekatan Alternatif yang Mengedepankan Keadilan Kolaboratif - Simandjuntak, Reynold; Singkay, Rafael (Jurnal Social Science, 2024)
This study aims to explore and analyze various Alternative Dispute Resolution (ADR) methods that can be used to resolve disputes in Indonesia, as well as to understand the effectiveness and challenges faced in their implementation. The research methods used include literature studies and normative legal research. The study’s results indicate that methods such as mediation and arbitration offer more flexible and efficient solutions compared to formal justice, with mediation being more suitable for disputes involving ongoing relationships, while arbitration provides a binding and final decision. In addition, E-Dispute Resolution shows great potential in increasing the accessibility and efficiency of dispute resolution, although challenges related to data security and regulations still need to be addressed. This study recommends increasing education and training on ADRs and developing regulations that support the implementation of this method in Indonesia.